Forming an Optimal Portfolio with a Single Index Model: Empirical study on banking stocks in the LQ45 Index - Suarjana, I Wayan; Surasmi, Ida Ayu (Jurnal Ekonomi dan Bisnis Jagaditha, 2024)
The aim of forming an optimal portfolio in this research is to determine the composition of the shares that form the portfolio. Apart from that, this research also aims to determine the expected return and risk of the portfolio being formed. The research sample is 5 banks included in the LQ45 Index. The data used is monthly stock prices. Data analysis uses a single index model, where the reference index is the Composite Stock Price Index on the Indonesian Stock Exchange. The results of the analysis found that there were shares of 4 banks that were included in the optimal portfolio. The proportion of each stock in the portfolio is as follows: Bank Mandiri 60.13%, Bank BRI 26.71%, Bank BCA 8.91%, and Bank BNI 4.25%. The portfolio formed is able to minimize risk compared to the shares that form the portfolio.